THE INFLUENCE OF PRODUCT QUALITY, BRAND IMAGE AND INTEGRATED MARKETING COMMUNICATION ON CUSTOMER VALUE AND ITS IMPLICATIONS ON CUSTOMER TRUST IN THE MODERN ORGANIC MARKET IN BOGOR CITY - Ramadhan, Muhammad Asrul; Limakrisna, Nandan; Muharam, Hari (Yayasan Education and Social Center, 2025)
Customer trust is a key factor in building long-term relationships between consumers and brands. This trust is developed through repeated positive experiences, consistent product quality, transparent communication, and a strong brand image. When customers feel confident that a brand or company can fulfill its promises and meet their expectations, they are more likely to remain loyal and recommend the product or service to others. This study aims to analyze the influence of product quality, brand image, and integrated marketing communication on customer value and its implications for customer trust in the modern organic market in Bogor City. The research method used is quantitative with a causality research approach. Data was collected through a survey using a questionnaire from 230 respondents, who are consumers aged over 17 years who shop at modern organic markets in Bogor City. Data analysis was conducted using structural equation modeling (SEM). The findings are expected to provide insights into effective marketing strategies for enhancing customer value and trust in organic products.